Peran ekonomi: Dampak dan peluang ekonomi Islam dalam peningkatan ekonomi berkelanjutan di Indonesia - Lestari, Nanda Aulia Winda (Maliki Interdisciplinary Journal, 2023)
Islamic economics is present and spread in various regions of Indonesia. Developments are increasingly creating elements of life marked by change, including in the economic field. Islamic economics is an increase in public awareness of religious values. The purpose of this study is to describe the impacts and opportunities of the sharia-compliant economy in improving the sustainable economy in Indonesia. In this study using a systematic research method that evaluates from journals. The results show that the Islamic economy has various impacts and opportunities in improving the economy in Indonesia. Islamic banks in Indonesia are one of the main economic improvement factors that are able to improve people's welfare with various principles. The existence of a sharia based economy is a fair and sustainable way of improving the economy. As an alternative economy, Islamic economics is able to encourage economic growth in Indonesia.